Mussel-Inspired Lego Approach for Controlling the Wettability of Surfaces with Colorless Coatings - Casagualda, Carolina (2022)
The control of surface wettability with polyphenol coatings has been at the forefront of materials research since the late 1990s, when robust underwater adhesion was linked to the presence of L-DOPA—a catecholic amino acid—in unusually high amounts, in the sequences of several mussel foot proteins. Since then, several successful approaches have been reported, although a common undesired feature of most of them is the presence of a remnant color and/or the intrinsic difficulty in fine-tuning and controlling the hydrophobic character. We report here a new family of functional catechol-based coatings, grounded in the oxidative condensation of readily available pyrocatechol and thiol-capped functional moieties. The presence of at least two additional thiol groups in their structure allows for polymerization through the formation of disulfide bonds. The synthetic flexibility, together with its modular character, allowed us to: (I) develop coatings with applications exemplified by textiles for oil-spill water treatment; (II) develop multifunctional coatings, and (III) fine-tune the WCA for flat and textile surfaces. All of this was achieved with the application of colorless coatings.